Structural and functional characterization of MBS301, an afucosylated bispecific anti-HER2 antibody. Issue 6 (18th August 2018) - Huang, Sijia; Li, Feng; Liu, Huifang; Ye, Pei; Fan, Xiaochuan; Yuan, Xinqiu; Wu, Zhidan; Chen, Jin; Jin, Chunyang; Shen, Beifen; Feng, Jiannan; Zhang, Boyan
ABSTRACT: MBS301, a glyco-engineered bispecific anti-human epidermal growth factor receptor 2 (HER2) antibody with a typical IgG1 monoclonal antibody structure, was developed through dual-cell expression and in vitro assembling process. MBS301 consists of two half antibodies engineered from trastuzumab and pertuzumab, respectively. Integrity and purity profiles of MB301 indicated that the heterodimerization of the two half antibodies was successful. The high and similar melting temperatures (Tm1, 72.0°C and Tm2, 84.8°C) of MBS301 compared with those of its parental monoclonal antibodies trastuzumab and pertuzumab (in-house made T-mab and P-mab, respectively) revealed its structural compactness. With computer-modeling experiments and Biacore binding and competition kinetics studies, the binding stoichiometry between MBS301 and HER2-ECD was determined to be 1:1 and the two arms of MBS301 were shown to bind to domains II and IV of HER2-ECD antigen simultaneously. MBS301 displayed synergistic bioactivities as the combination of T-mab and P-mab in vitro in multiple cancer cell lines and in vivo in xenograft mouse model studies, and showed more effective activity than T-mab or P-mab used individually. Moreover, fucose-knockout dramatically increased MBS301's binding affinity to low affinity FcγRIIIa allotype 158F (KD  = 2.35 × 10 −7 M) to near the high affinity level of allotype V158 (KD  = 1.17 × 10 −7 M). This resulted in far more effective ADCC activity of MBS301 than the combination of T-mab and P-mab in killing HER2-positive cancer cells. Hence, a novel fully afucosylated anti-HER2 bispecific antibody with improved antitumor activities was generated and shown to have the potential to be used for treating HER2-positive but trastuzumab-resistant solid tumors.